TANGGUNG JAWAB NOTARIS ATAS DOKUMEN DIBAWAH TANGAN YANG DIBERI TANDA (WAARMERKING) YANG TANDA TANGANNYA DIPALSUKAN OLEH PARA PIHAK. - Entin, Entin; Halim, Anriz Nazaruddin; Ridwan, Rifki (SENTRI: Jurnal Riset Ilmiah, 2023)
This study aims to explore the responsibilities of notaries in relation to documents under signed hands (waarmerking), particularly in contexts where signatures on such documents are forged by the parties. where tried to answer the question, "What is the responsibility of the notary in cases where the signature on the document under the hand forged by the parties?"That the notary has legal responsibility for the validity of the signature on the document and can be held liable if it is confirmed that the signature was forged. This hypothesis also aims to explore the steps or procedures that can be taken by notaries to prevent and overcome cases of false signatures on documents under a signed hand (waarmerking). The research methodology employed in this study is normative juridical research, which combines interviews with library law research utilizing primary, secondary, and tertiary legal sources. The research approach encompasses the Statute Approach, Conceptual Approach, Analytical Approach, and Case Approach. The technique used to gather legal materials involves identifying and cataloging positive legal rules, literature books, journals, and other relevant legal sources. The analysis of legal materials involves legal interpretation, systematic interpretation, and legal construction methods. In the process of waarmerking documents under falsified hands, the notary acts as a witness who only confirms the agreement of the parties and records it on the deed he books, without being responsible for the content of the document or the authenticity of the signature. Even if the signature on the document turns out to be fake, criminal liability cannot be imposed on the Notary as a public official, since the notary does not have the authority to review the validity or invalidity of the handwritten document submitted to him. In terms of legal certainty, waarmerking by a notary aims to ensure that the legal acts recorded are in accordance with the actual legal requirements, even if the authenticity of the documents is later proven to be false. The principle of" geen bevoegdheid zonder veraantwoordelijkheid " asserts that there is no authority without liability, however, in this case, the notary does not have the authority to review the authenticity of the documents submitted by the parties facing him